Low Decision Space Means No Decentralization in Fiji; Comment on "Decentralisation of Health Services in Fiji: A Decision Space Analysis" - Jean-Paul Faguet (Kerman University of Medical Sciences, 2016)
Mohammed, North, and Ashton find that decentralization in Fiji shifted health-sector workloads from tertiary hospitals to peripheral health centres, but with little transfer of administrative authority from the centre. Decisionmaking in five functional areas analysed remains highly centralized. They surmise that the benefits of decentralization in terms of services and outcomes will be limited. This paper invokes Faguet's (2012) model of local government responsiveness and accountability to explain why this is so - not only for Fiji, but in any country that decentralizes workloads but not the decision space of local governments. A competitive dynamic between economic and civic actors that interact to generate an open, competitive politics, which in turn produces accountable, responsive government can only occur where real power and resources have been devolved to local governments. Where local decision space is lacking, by contrast, decentralization is bound to fail because it has not really happened in the first place.